(untitled) - Turabian, Kate L. (Chicago, 1987)
The Manual retains its familiar three-part structure, beginning with an overview of the steps in the research and writing process, including formulating questions, reading critically, building arguments, and revising drafts. Part II provides an overview of citation practices with detailed information on the two main scholarly citation styles (notes-bibliography and author-date), an array of source types with contemporary examples, and detailed guidance on citing online resources.
Keywords: Dissertations, academic,Luận văn, học tập